Engaging African American Women in Community-Based Health Promotion Programs: Key-Informant Recommendations. Issue 3 (3rd July 2018) - Holt, Jeana M.; Johnson, Teresa S.; Zabler, Bev
ABSTRACT: This explorative qualitative study describes the lived experiences of urban-dwelling African American (AA) women who participated in a nurse-led community-based health-promotion program for up to 20 years. Data were collected using semistructured interviews and analyzed using a phenomenological approach. Two central themes arose, the program facilitated behavior change and supported retention and recruitment. The findings suggest that AA women will attend classes and invite other participants when facilitators embed relevant community-engaged principles in the program. The participants recommended essential elements that supported the longevity of the program. Future studies may determine if these suggestions resonate with other AA women.